Host specificity of Selenidium pygospionis (Archigregarine Apicomplexa) - Alale, Theophilus (2019)
In order to understand potential co-evolution between a parasite and its host, this study was conducted to investigate whether the apicomplexan parasite Selenidium pygospionis, specifically infects the polychaete worm, Pygospio elegans or if it has a broader distribution in other polychaete species. In addition, I analyzed the diversity of the mitochondrial cytochrome c oxidase subunit I (COX-I) gene in both the host and parasite from different populations in Europe. Species specific primers were used in ddPCR to identify the presence of S. pygospionis in polychaete species obtained from Finland, Scotland, Denmark and Iceland. With additional species specific primer pairs, ABI Sanger sequencing method was used to generate 548 bp sequences from the apicomplexan COX-I gene. Genetic diversity in COX-I was compared to that determined from DNA sequence data from P. elegans in order to compare the genetic diversity between the host (P. elegans) and the parasite (S. pygospionis). The ddPCR assay suggested that Marenzelleria species had higher levels of amplified apicomplexan COX-I compared to other species sampled. However, sequences obtained from the amplicon did not verify the result. The genetic diversity for both species was low as was the interpopulation and intrapopulation genetic distances. These results indicate that S. pygospionis is a specific parasite of Pygospio elegans despite the fact that other species are likely exposed to the parasite’s oocysts in the environment. Moreover, the COX-I gene may not be sufficient to separate different Selenidium species. It will therefore require that other coding genes such as Cytochrome b (Cytb) and COX-III be tried before conclusive inference.